Universal Flu mRNA Vaccine: Promises, Prospects, and Problems - Andrei A. Deviatkin; Ruslan A. Simonov; Kseniya A. Trutneva; Anna A. Maznina; Elena M. Khavina; Pavel Y. Volchkov (Vaccines, 2022)
The seasonal flu vaccine is, essentially, the only known way to prevent influenza epidemics. However, this approach has limited efficacy due to the high diversity of influenza viruses. Several techniques could potentially overcome this obstacle. A recent first-in-human study of a chimeric hemagglutinin-based universal influenza virus vaccine demonstrated promising results. The coronavirus pandemic triggered the development of fundamentally new vaccine platforms that have demonstrated their effectiveness in humans. Currently, there are around a dozen messenger RNA and self-amplifying RNA flu vaccines in clinical or preclinical trials. However, the applicability of novel approaches for a universal influenza vaccine creation remains unclear. The current review aims to cover the current state of this problem and to suggest future directions for RNA-based flu vaccine development.